2003
DOI: 10.1097/00003226-200308000-00019
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy in the Patients With Cornea Farinata

Abstract: In vivo corneal confocal microscopy is useful for observing stromal abnormalities in cornea farinata. Further investigation of posterior stromal opacities using confocal microscopy may be useful to understand and differentiate various corneal conditions involving primarily deep stromal layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…They are best seen on retro-illumination and appear grey-brown to white in color. 30 Kobayashi et al 31 reported two cases with cornea farinata. Using IVCM, highly reflective small particles were observed in the cytoplasm of keratocytes in the deep stroma adjacent to the corneal endothelial layer.…”
Section: Resultsmentioning
confidence: 99%
“…They are best seen on retro-illumination and appear grey-brown to white in color. 30 Kobayashi et al 31 reported two cases with cornea farinata. Using IVCM, highly reflective small particles were observed in the cytoplasm of keratocytes in the deep stroma adjacent to the corneal endothelial layer.…”
Section: Resultsmentioning
confidence: 99%
“…Also, no evident abnormalities could be detected in Descemet membrane and endothelium level. [10][11][12][13][14] Another differential diagnosis includes fleck dystrophy, which is a rare autosomal dominant corneal stromal dystrophy with discrete opacities similar to those of cornea farinata or pre-Descemet dystrophy. However, the opacities are not limited to the posterior stroma but are found throughout the entire corneal stroma by slit-lamp biomicroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…1 We and many others have previously demonstrated that in vivo whitelight corneal confocal microscopy provides noninvasive, realtime images with high resolution and contrast of all layers in both normal and diseased corneas. [2][3][4][5][6][7] However, confocal microscopy has so far been limited to investigations of the cornea. We have also recently demonstrated that the in vivo laser confocal microscope (Vivascope 1000, Lucid Inc., Henrietta, NY) can be used to observe the bulbar conjunctiva in both rabbits 8 and humans, 9 which could not be achieved by conventional white-light confocal microscopy.…”
mentioning
confidence: 99%